(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
The Transdanubian Central Range (TCR) is a flattened range of hills in northern Transdanubia (Hungary), formed mainly by Mesozoic carbonate rocks showing strong facies similarities with the Southern Alps and the Austroalpine domain. The Jurassic system is divided into several formations of predominantly pelagic limestones. Ammonoids are frequent and were collected bed-by-bed in numerous sections, providing an excellent biostratigraphic resolution. The thickness of the Jurassic system is usually small but changes along the strike of the TCR. It reaches a maximum thickness of 500 m in the western part; is very variable (10-400 m) in the central segment (Bakony Mts.) and rather low (less than 100 m) in the east (Gerecse). In the Bakony segment, the thickness variation reflects the strongly dissected topography of the Jurassic sea-floor. Synsedimentary tectonics is dominated by normal faults; tilted blocks and listric faults may be inferred only in the east. Five main steps were identified in the palaeogeographic evolution: 1) Late Hettangian: carbonate oolitic shoals prevail, except for a few sites where non-deposition or neritic sediments occur. 2) Sinemurian and Pliensbachian: tectonic disintegration resulted in an intricate pattern of submarine horsts and intervening basins, with condensed sedimentation or non-deposition on the horsts and thicker, continuous sedimentary sequences in the basins. The submarine topographic highs are surrounded by aprons of redeposited material (scarp breccias, brachiopod coquinas, crinoidal calcarenites, spiculitic cherty limestones), while pure or argillaceous limestones (Rosso Ammonitico) prevail in the distal areas. 3) Early Toarcian: the Tethys-wide anoxic event is superimposed on the previous submarine bottom topography; the resulting black shales and sedimentary Mn-ores are concentrated on the western sides of some horsts. 4) Dogger to Early Malm: radiolarites with heterochronous lower and upper boundaries (Aalenian to Kimmeridgian) prevail, except for the top of some submarine topographic highs. The absence of uppermost Bathonian to Lower Oxfordian carbonates suggests that the whole TCR sunk below the CCD in those times. 5) Latest Jurassic: the uniform deposition of Rosso Ammonitico and Biancone in the Late Kimmeridgian and Tithonian is interrupted only in the Early Tithonian by local intercalations of scarp breccias and coarse biodetrital limestones. This is interpreted as the last manifestation of synsedimentary tectonic movements along the faults bordering the submarine horsts. Based on palaeogeographic similarities and analogies in Jurassic times, the TCR is visualized as the northern foreground of the Trento platform/plateau (lying north of the later Insubric lineament), where the block-tectonic disintegration and differential subsidence started earlier and resulted in a bottom morphology more dissected than in the South Alpine part of this west Tethyan passive margin.